ANALISIS BAHASA KEKINIAN PADA MAHASISWA STKIP PARIS BARANTAI KOTABARU - Normasunah Normasunah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
This method of this research is qualitative with a descriptive approach. Sources of data in this study are the results of conversations by fellow students of STKIP Paris Barantai Kotabaru with the technique of recording and collecting the current language heard. The results showed that there were 8 types of contemporary language types used by students of STKIP Paris Barantai Kotabaru namely contemporary words in the form of abbreviations, contemporary words in the form of warm words, contemporary words that have meaning according to dictionaries but change meaning, contemporary words that get influences from foreign languages, contemporary words that appear as a result of certain events, contemporary words in the form of opposite words, spoiled contemporary words and contemporary words whose letters change. Keyword: Language and Current Language.